PEMBERDAYAAN MASYARAKAT UNTUK MENINGKATKAN KEMANDIRIAN DESA MELALUI BUDIDAYA HIDROPONIK DI KELURAHAN SURYA TIMUR KECAMATAN SUNGAILIAT - Iken Setiawan; Adinda; Ahmad Nur Hidayah; Dyna Safyah; Herna Saputri; Nurul Janah; Desy Yuliana Dalimunthe (Universitas Mataram, 2023)
Thematic Real Work Lectures (KKN-T) are one type of program from the Merdeka Belajar – Merdeka Campus (MBKM) implemented by Bangka Belitung University. KKN-T was accompanied by Mrs. Desy Yuliana Dalimunthe, S.E., M.Sc. as a Field Supervisor with 12 members and located in Surya Timur Village, Sungaliat District, Bangka Regency. Hydroponic cultivation is one of the additional work programs being implemented. Hydroponic cultivation is a method of cultivating plants using water, nutrients and oxygen. This program aims to be a form of village independence through proper management of the hydroponic system by a team of PKK women which can become one of the PKK work programs in the East Surya sub-district. Community empowerment is carried out using direct observation through outreach in the form of socialization and hydroponic cultivation practices. The targets of this activity include PKK women to optimize vegetable cultivation activities for the community. The hydroponic method used is the Nutrient Film Technique (NFT) method. In the hydroponics process, it starts with preparing tools and materials and then designing the hydroponic installation. Next, sow in rockwool, then sow the seeds within 3-4 days. After sowing, the seedlings will be moved to the installation into a netpot attended by the Village Head in Surya Timur Subdistrict and accompanied by a hydroponic coach. As a future follow-up, maintenance will be carried out on hydroponic plants until the plants are ready to be harvested and distributed to PKK women and East Surya Village officials during harvest activities. The conclusion from this activity is that hydroponic cultivation in general can be developed by the surrounding community and sub-district officials.